A method of detecting level change of uranium fluorination mixture in the hopper by gamma-ray dose. (August 2021) - Lei, JieHeng; Lei, Lin; Qin, QianQian; Yin, Zeyuan; Lei, ZeYong
Abstract: The measurement of material level change in uranium fluorination has an essential influence on uranium production quality. In this study, a method to determine the level change of uranium fluorination mixture in the hopper by online radiation meter outside hopper is established. We have designed an experiment to study the change of radiation field outside the hopper with a known height of radioactive material to discover its regular pattern. The experimental results show that when the probe is placed 50 mm away from the cylinder wall, the average radiation dose is more significant, and the change of radiation dose measured by the instrument at this position is more evident than that at other positions. Then through the measurement of the external radiation field of the hopper with unknown material level to estimate the material level, and by opening the cover of hopper to verify the accuracy of the material level measurement method. Based on the experimental results and theoretical analysis, a method and formula for judging the mixture material are proposed. This method can quickly determine the level of uranium fluoride mixture in the hopper online, realize the accurate control of material parameters in the process of uranium conversion, and improve the quality of uranium conversion products. Highlights: A method of using gamma-ray dose Instruments to ensure optimal uranium fluorination is proposed. The change of gamma radiation field outside the uranium fluorination hopper has been analyzed and visualized through amounts of data, which provides basis for the establishment of radiation field model. A mathematical model suitable for monitoring liquid level in uranium fluoride hopper is established.